The rate of force development scaling factor: a review of underlying factors, assessment methods and potential for practical applications - Kozinc, Ž.; Smajla, D.; Sarabon, N. (European Journal of Applied Physiology, 2022)
When humans perform isometric ballistic contractions of different intensities, a strong linear relationship is observed between peak force and peak rate of force development. The slope of this relationship, termed the rate of force development scaling factor (RFD-SF), has been proposed as a measure of neuromuscular quickness of submaximal contractions. The RFD-SF is largely dependent on motor unit firing rate and its modulation with contraction intensity, and possibly by agonist-antagonist coordination. The purpose of this review was to critically evaluate the available literature on RFD-SF, including the underlying physiological mechanisms, assessment protocols and methodological considerations, practical application to clinical and sports practice and additional factors such as sex, muscle group, task and fatigue. The main findings of the review are: (a) RFD-SF is very sensitive to impairments associated with aging and neurological diseases, (b) the literature lacks studies on the importance of RFD-SF for athletes, with some evidence that RFD-SF may affect the accuracy of submaximal movements, (c) RFD-SF is not largely influenced by fatigue and sex, (d) the RFD-SF values have been very consistent across muscle groups, with an exception of ankle muscles, (e) the methodology for RFD-SF assessment appears to be well established and standardized. Future research is needed to determine if RFD-SF provides any independent information that cannot be captured with peak force/torque and RFD.